АНАЛІЗ СУЧАСНИХ МЕТОДІВ РОЗБУДОВИ ІНФОРМАЦІЙНИХ ПОРТАЛІВ НАУКОВО-АКАДЕМІЧНОЇ УСТАНОВИ - Кулаківський, Володимир; Скворцов, Іван; Давидов, Олександр (Институт сверхтвердых материалов им. В. Н. Бакуля Национальной академии наук Украины, 2024)
The subject of the article's research is the analysis of modern approaches to the development of information portals of scientific and academic areas. The article examines the modern requirements for web portals, the existing functionality of the sites and portals of the leading scientific institutions of the National Academy of Sciences, the methods and software used to develop these portals. General recommendations for the modernization of the existing INM web portal and its integration with social networks, methods and means by which this modernization can be carried out are proposed.